IMPLIKASI GAYA KEPEMIMPINAN TRANSFORMASIONAL, IKLIM ORGANISASI DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN DI PURI SARON HOTEL SEMINYAK - Ni Made Dwi Priskilla; I Putu Santika (Journal of Applied Management Studies, 2020)
Transformational leadership style is one of the leadership styles that can make changes to the company. Changes made by the leadership must be able to improve employee performance, as well as enhance teamwork between departments. Positive changes will form a positive organizational climate so if negative changes will give the organizational climate to the company to be negative This research uses quantitative research, which was carried out at Puri Saron Hotel Seminyak. The author conducted research by observation, interviews and questionnaires with a sample size of 100 respondents. This research was conducted to find out how big the implications of the transformational leadership style, organizational climate and teamwork on employee performance. The results of the research on hypothesis testing, the transformational style variables and teamwork have positive and significant implications for employee performance, whereas the organizational climate variable does not have a positive effect on employee performance.